The Role of Store Atmosphere and Price on Purchasing Decisions at MSME Cafes In Tebing Tinggi City as Supporters of a Sustainable Local Economy - Sigit Arya Pranata; Hafizh Rabiula; Dedy Dwi Arseto; Willy Cahyadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to examine and analyze the influence of store atmosphere and price on purchasing decisions at MSME cafés in Tebing Tinggi City as a support for sustainable local economic development. This research employed a quantitative method. The study was conducted in Tebing Tinggi City from December 2025 to April 2026. The research population consisted of all consumers of MSME cafés in Tebing Tinggi City, whose total number was unknown. The sample size was determined using Cochran’s formula, resulting in 96 respondents selected through an accidental sampling technique. The study utilized primary data collected through questionnaire distribution. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS, including outer model testing, inner model testing, and hypothesis testing. The results indicate that store atmosphere has a positive and significant effect on purchasing decisions. Price also has a positive and significant effect on purchasing decisions. Simultaneously, store atmosphere and price have a positive and significant effect on purchasing decisions at MSME cafés in Tebing Tinggi City. These findings suggest that a comfortable café atmosphere and appropriate pricing can enhance consumers’ purchasing decisions.